Between Decentralization and Control: How Cryptocurrency is Redefining Global Financial Architecture - Mohammed Dawood Dawood; Syed Saif Ullah Hussaini; Mohd Zain ul Abeddin; Bishal Hizli Hizli (PT Agung Media Publisher, 2026)
Cryptocurrencies have emerged as a disruptive force in global finance, challenging traditional banking systems through decentralization, transparency, and borderless transactions. Initially perceived as speculative assets, cryptocurrencies have increasingly gained institutional recognition, raising important questions regarding their financial role, regulatory governance, and long-term sustainability. This study adopts a qualitative-dominant mixed-method approach based on secondary data analysis. Data were collected from peer-reviewed journals, institutional reports, regulatory documents, and reputable market analyses published over the last decade. Thematic and descriptive analyses were employed to examine trends in cryptocurrency adoption, regulatory responses, technological innovation, and sustainability efforts. The findings indicate that cryptocurrencies have evolved into recognized financial assets, with growing institutional participation and expanding applications in cross-border payments and decentralized finance. However, significant challenges persist, including regulatory fragmentation, cybersecurity risks, market volatility, and environmental concerns related to energy-intensive mining. Regulatory milestones such as the European Union’s MiCA framework demonstrate progress toward legal harmonization, while technological innovations such as Layer 2 solutions, interoperability protocols, and Proof-of-Stake consensus mechanisms support scalability and sustainability. The discussion links these findings to Technology Acceptance and Innovation Diffusion theories, showing that institutional adoption is driven by perceived usefulness, regulatory legitimacy, and technological compatibility. Market Regulation and Institutional theories further explain divergent national regulatory approaches and increasing global coordination efforts. Sustainability considerations emerge as a critical determinant of long-term viability, shaping both technological development and policy intervention. Cryptocurrencies represent a transformative element of the global financial system, offering opportunities for efficiency, inclusion, and innovation.